Fibrillin Containing Elastic Microfibrils Support Platelet Adhesion under Dynamic Shear Conditions - Ross, Julia M.; McIntire, Larry V.; Moake, Joel L.; Kuo, Huey-Ju; Qian, Rui-Qing; Glanville, Robert W.; Schwartz, Elaine; Rand, Jacob H. (Thrombosis and Haemostasis, 1998)
The vascular subendothelium contains macromolecular structures called microfibrils. Type VI collagen is one protein found in microfibrils that supports platelet adhesion and aggregation and we have previously evaluated the roles of platelet receptors and vWf involved in these processes under physiological shear conditions. Here we investigate the ability of fibrillin containing elastic microfibrils to support mural thrombus formation. Our results show that elastic microfibril surfaces support platelet adhesion under low shear conditions at a level similar to collagen VI tetramers. However, the degree of aggregation on the elastic microfibril surface is much higher. Both adhesion and aggregation were shown to be mediated by the GPIIb-IIIa platelet receptor. Elastic microfibrils do not support the formation of mural thrombi under high shear conditions. These results suggest roles for both collagen VI and fibrillin containing elastic microfibrils in modulating the platelet response to blood vessel injury.